2008
DOI: 10.1099/vir.0.83393-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of low-concentration chlorine dioxide gas against influenza A virus infection

Abstract: Influenza virus infection is one of the major causes of human morbidity and mortality. Between humans, this virus spreads mostly via aerosols excreted from the respiratory system. Current means of prevention of influenza virus infection are not entirely satisfactory because of their limited efficacy. Safe and effective preventive measures against pandemic influenza are greatly needed. We demonstrate that infection of mice induced by aerosols of influenza A virus was prevented by chlorine dioxide (ClO2) gas at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 39 publications
0
65
0
3
Order By: Relevance
“…However, the use of NaClO brings several disadvantages including its irritating and toxic effects and efficacy in a limited pH range. In contrast, ClO 2 is an efficient disinfectant and is less toxic, less irritant, effective in a wide pH range, can be used as both liquid and gas (16), and produces fewer trihalomethane compounds (12). It has been demonstrated that the mode of action of ClO 2 is via protein denaturation and involves the covalent oxidative modification of tryptophan and tyrosine residues (6).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of NaClO brings several disadvantages including its irritating and toxic effects and efficacy in a limited pH range. In contrast, ClO 2 is an efficient disinfectant and is less toxic, less irritant, effective in a wide pH range, can be used as both liquid and gas (16), and produces fewer trihalomethane compounds (12). It has been demonstrated that the mode of action of ClO 2 is via protein denaturation and involves the covalent oxidative modification of tryptophan and tyrosine residues (6).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that ClO 2 can inactivate both gram-positive (S. aureus) and gram-negative (E. coli) bacteria. Ogata and Shibata [17] also demonstrated that low-concentration ClO 2 gas (0.03 ppm) can protect mice against influenza virus infection, which suggests that this gas could also be used to control viral infections. This finding also suggests that ClO 2 can inactivate viruses with envelopes, such as influenza virus.…”
Section: Discussionmentioning
confidence: 99%
“…Ogata et al also demonstrated in other experiments that this level of ClO 2 gas had no adverse effects on rats [25,26] . In fact, in the mouse experiment described above [24] , all of the mice subjected to the experiment appeared very healthy during and after exposure to 30 ppb ClO 2 gas.…”
Section: Introductionmentioning
confidence: 99%
“…Ogata and Shibata [24] recently reported that very lowconcentration ClO 2 gas prevented infections of the influenza virus in a mouse infection model. The concentration of the gas used in this experiment was as low as 30 parts per billion (ppb, volume/volume).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation